EFFECT OF EQUILIBRATION DURATION, VAPOUR TEMPERATURE AND EXPOSURE VAPOUR DURATION ON CRYOPRESERVED SPERM OF AFRICAN CATFISH - K., Noor Azlina,; W.E., Wan Khadijah,; R.B.2, Abdullah, (Malaysian Journal of Science, 2012)
The objective of this study was to obtain the optimal freezing rate with special focus on equilibration duration, vapour temperature and exposure vapour duration on sperm motility characteristics (SMCs) of African catfish (Clarias gariepinus) using Fish-Ringer Extender (FRE) with fixed 10% Dimethyl-sulfoxide (DMSO) as cryoprotectant. Briefly, the straws containing the sperm were placed in a refrigerator at 4oC with three equilibration durations (120, 140 or 160 min) after which exposed to liquid nitrogen vapour at three vapour temperatures (-80, -90 or -100oC) with three exposure vapour durations (5, 10 or 15 min). Finally, the straws were directly plunged into liquid nitrogen vapour at -196oC. The frozen sperm were thawed at 30oC for 30 sec to evaluate the sperm movement characteristics using the Automated Semen Analyzer-IVOS (Hamilton Thorne, USA). Results showed that the highest values of total motility and progressive motility obtained were combination factors of 120 min equilibration duration, -100oC vapour temperature and 15 min vapour exposure duration (87.44 ± 2.07% and 28.22 ± 2.16%, respectively). Combination of 120 min, -100oC and 15 min gave the highest value of rapid velocity (38.56 ± 3.10%), while combination of 120 min, -80oC and 10 min gave the lowest value (16.33 ± 3.21%). The highest values of Velocity Average Path (VAP), Straight-line Velocity (VSL) and Curvilinear Velocity (VCL) were attained by combination of 120 min, -80oC and 15 min which produced 68.76 ± 6.42%, 60.49 ± 6.01% and 94.71 ± 6.27%, respectively. For combination of 120 min, -100oC and 15 min was probably the optimum condition in which positive correlations were shown between total motility and progressive motility; total motility and rapid; total motility and VAP; total motility and VSL; total motility and VCL; progressive motility and rapid; progressive motility and VAP; progressive motility and VSL; progressive motility and VCL; rapid and VAP; rapid and VSL; rapid and VCL; static and Straightness (STR); VAP and VSL; VAP and VCL; VSL and VCL and STR and Linearity (LIN) (p > 0.05). In conclusion, under the present conditions, the optimal frozen-thawed sperm motility characteristics in African catfish using FRE extender was obtained with combination of 120 min equilibration duration, -100oC vapour temperature and 5 to 15 min exposure vapour duration. It is recommended that FRE extender using DMSO as cryoprotectant apparently is suitable to cryopreserve the sperm of African catfish (Clarias gariepinus).